Logical automatic implementation of steganographic coding algorithms (Journal of Mathematics Mechanics and Computer Science, 2024)
The main goal of steganography is to ensure secure communication while keeping the communicative act "invisible". The origin of this term dates back to Ancient Greece and translates as "hidden writing". A simple yet effective method of steganography in antiquity, considering the frequent use of wax tablets, involved cutting out the message on the wooden bottom of the tablet and then writing a decoy message on the wax. Technological evolution has led to human ingenuity, allowing the use of this powerful tool for both message transmission and watermarking products during the transition from physical to digital media. There are various forms of steganography, including injective, generative, substitutive, selective, and constructive. The steganography we employ is injective, as it is more suitable for our task of hiding information in image pixels. After various searches, we decided to use BMP (Bitmap Picture) 3 (Microsoft Windows NT) and later versions as the image file format, as this version, especially in 24-bit and 32-bit encodings, represents a single color component. Each byte allows for altering the least significant bits without changing the external appearance of the image.
Keywords: Logical automatic implementation; steganographic coding; algorithms; RGB (Red, Green, Blue); LSB (Least Significant Bit); PSNR (peak signal to-noise ratio)